Oncoplastic Surgery as an Alternative in the Treatment of Patients with Breast Cancer - Tatiana Hernández González; Miguel Ángel Amaró Garrido; Yurisbel Tomás Solenzal Álvarez; Ana Lucía Martínez Hernández (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Background: plastic surgery helps to improve the quality of life of patients with breast cancer. Breast reconstruction has evolved not only in aesthetic matters, but also in favor of achieving less morbidity in each patient affected. Objective: to describe the results obtained with the application of oncoplastic techniques in patients with breast cancer. Method: a descriptive study of a series of 41 patients was carried out at the Camilo Cienfuegos Provincial General Hospital in Sancti Spíritus from March 2018 to October 2020. The sample included all the patients operated on for breast cancer in which techniques were performed. Conservative and radical oncology, as well as, plastic surgery. Demographic, clinical and therapeutic variables were analyzed. The arithmetic and tabular procedures of descriptive statistics were used. Quantitative variables were shown as means and standard deviation. Qualitative data such as frequencies and percentages. Results: the mean age was 45 years, with a minimum of 26 years and a maximum of 67. In patients without previous breast deformity, radical and conservative treatments, reconstruction with skin-sparing surgery and mastoplasties with minimal incisions were applied. In patients with major deformities, the predominant treatment was conservative and reconstructions with mastoplasties. The tumor stages that prevailed were T2N1M0 and T1N1M0. The highest number of complications was observed in patients undergoing skin-sparing surgery and in those with radical treatments. Conclusions: oncoplastic surgery is an alternative surgical treatment that is currently used more frequently in patients with breast cancer. Similar results are obtained to conventional surgery in terms of incidence of complications, recurrences and death.